Streptococcus agalactiae isolates FROM SUBCLINICAL MASTITIS CATTLE : I. In vitto phenotypic expression of isolates - Iwan H. Utama; Ninuk S. Rejeki; I Made Sukada; I Wayan T. Wibawan (Media Veteriner, 1997)
Thirty six isolates Streptococcus agalactiae from subclinical mastitis cattle in Bogor were esanlincd their phenotypic espressions such as hemolytic pattern. supernatant turbidity inliquid medium, and colony morphology in semisolid medium (agar semi solid). Nine, fifteen and ttvelve isolates showed their a, 0, and y hemolytic patterns respectively. Fourteen isolates showed turbid supernatant, 18 isolates with less turbid supernatant, and the rest gave clear supernatant in fluid medium. In agar semi solid, 15 isolates showed mostly thick diffuse colonies in combination with thin diffuse and compact colonies, 17 isolates with mostly thin diffuse colonies in combination with thick diffuse and compact colonies. The rest isolates showed compact without diffuse colonies. There was a relation between growth pattern in fluid medium and colony morphology in agar semi solid, and the varia